2020
DOI: 10.1016/j.ssmph.2020.100683
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and spatial distribution of the co-occurrence of childhood anaemia and stunting in Ghana

Abstract: Childhood anaemia and stunting are major public health concerns in Ghana. Using the 2014 Ghana Demographic and Health Survey, we evaluated whether childhood anaemia (Haemoglobin concentration < 110 g/L) and stunting (height-for-age z score < −2) co-occur beyond what is expected in Ghana, and employed spatial analysis techniques to determine if their co-occurrence is spatially correlated. There was no statistically significant difference between the observed and expected frequency of co-occurrence. Among 24–35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
6
9
0
Order By: Relevance
“…The study further found a high risk of anaemia among children living in the poorest, poorer and middle households compared to the richest household wealth index. The findings of this study are consistent with the findings of previous studies in Ghana [ 32 , 33 ], sub-Saharan African countries [ 30 ], Malawi [ 16 ], Guinea [ 34 ] and India [ 35 ]. The likely explanation for this phenomenon is the assumption that poorer household heads in economically disadvantaged countries are economically stressed and nutritionally vulnerable to a greater extent than richer households.…”
Section: Discussionsupporting
confidence: 93%
“…The study further found a high risk of anaemia among children living in the poorest, poorer and middle households compared to the richest household wealth index. The findings of this study are consistent with the findings of previous studies in Ghana [ 32 , 33 ], sub-Saharan African countries [ 30 ], Malawi [ 16 ], Guinea [ 34 ] and India [ 35 ]. The likely explanation for this phenomenon is the assumption that poorer household heads in economically disadvantaged countries are economically stressed and nutritionally vulnerable to a greater extent than richer households.…”
Section: Discussionsupporting
confidence: 93%
“…These studies show that economic and environmental factors including economic inequalities at the household level, maternal educational and occupational status, household hygiene, rural-urban residence, and access to health care services, are associated with childhood stunting in Ghana [ 10 15 ]. Additionally, demographic factors such as maternal and child age, sex, birth interval, parity, marital status, and the number of household members, among others, are also associated with childhood stunting [ 11 , 16 18 ]. Nonetheless, the associative effects of the socio-ecological covariates which operate at the community level have not been systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…This is an indication that despite the decline, stunting continues to affect the lives of many children in the country [9]. Given the high level of childhood stunting in Ghana, both small-and large-scale studies have examined its socio-demographic determinants [10][11][12][13][14][15]. These studies show that economic and environmental factors including economic inequalities at the household level, maternal educational and occupational status, household hygiene, rural-urban residence, and access to health care services, are associated with childhood stunting in Ghana [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, approximately 159 million children under 5 years are stunted, with more than 90% of them living in low-and middle-income countries (9). Worldwide, nearly 200 million children under the age of 5 are stunted, underweight, or a mixture of both (10).…”
Section: Introductionmentioning
confidence: 99%